Identification of The Lohman Brown Strain Purebred Chicken's Eggshells Based on Egg Age - Qurniawan, Anas; Firnanelty, Firnanelty; Busrah, Zulfiqar; Baso Kaswar, Andi; Hifizah, Amriana; Astati, Astati; Rusny, Rusny (Universitas Sulawesi Barat, 2024)
This study aimed to identify the shell quality of Lohman brown strains. A total of 460 eggs aged 1–14 days from Lohman brown strains were collected from community farms in Gowa, South Sulawesi, Indonesia. The study variables included egg weight, egg index, shell weight, thickness, and percentage. Analysis was conducted using analysis of variance (ANOVA), and the difference in shelf life was analyzed using Duncan's multiple range test. The results revealed that egg weight, egg index, shell weight, shell thickness, and shell percentage significantly (P<0.05) affected egg age from 1 to 14 days. The study concluded that older Lohman Brown strain chicken eggs have reduced weight and shell thickness. Additionally, egg age significantly impacts shell weight, but shell thickness decreases as the egg ages. The color classification of eggshells over 14 days, as indicated by hex codes and sRGB values, shows significant variation, with the darkest brown occurring on days 6 and 11 and the lightest brown on day 1.